The Scholarly Pathfinder: Andō Hideharu’s “Weba kikō” (Max Weber: A Travelogue, 1972) - Wolfgang Schwentker (Historicka Sociologie, 2025)
In 1969/70, Andō Hideharu (1921–1998), a Japanese historian of ideas, was a visiting professor at the Max Weber-Institute in Munich, Germany, for a period of one year. He was a harsh critic of Marianne Weber’s 1926 biography of her husband. During his tenure, he travelled to a number of places associated with Max Weber, with the aim of reconstructing his personal history. Andō literally followed Weber’s path from the cradle to the grave, though not necessarily in a chronological order. In a travelogue published in 1972, Andō recounted his experiences in Germany, Switzerland, Austria, and France, with a particular emphasis on interviews conducted with contemporaries of Max Weber who were still alive in 1969/70. Andō’s primary concern was in the personality of Max Weber, with a secondary focus on Weber’s work and the adaptation of Weber’s sociology for the study of Japanese modernity. The following article reconstructs Andō’s travel experiences in Europe by analysing his “Weber Travelogue”. It then discusses a bitter controversy that arose between Andō and certain colleagues in the context of Japanese Weber studies upon his return to Japan. Finally, the article assesses the merits and limitations of Andō’s “time travel” into Max Weber’s life through the lens of “Motivenforschung” (study of motives), a concept he drew from Weber’s methodological writings.